Review of the business strategy to facilitate 3-UK to monetise mobile internet and explore new business models to leverage those strategies. - Nambiar, Manoj (2009)
“Mobile Internet Services Booming” (ComScore, April 9, 2009). As of 2007, the number of PC users in the world has exceeded 1 billion and there are 1.5 billion internet users globally. At the same time, there are more than 4 billion mobile subscribers, indicating the vast growth potential for mobile internet, especially considering that 58% of the PCs are in market that account for 15% of the world population. This means mobile will be the internet terminal for majority of the users. Global migration to Third Generation (3G) is also picking up the pace and it leaves a huge growth potential for the mobile internet. According to the analysts, Nielsen Online, rate of mobile internet in the UK is growing 8 times faster than internet use on computers. Hence, most of the mobile operators are strategically positioning themselves to capitalise on this growth of the mobile internet.